Prevalence of maternal near miss and community-based risk factors in Central Uganda. Issue 2 (November 2016) - Nansubuga, Elizabeth; Ayiga, Natal; Moyer, Cheryl A.
Abstract: Objective: To examine the prevalence of maternal near-miss (MNM) and its associated risk factors in a community setting in Central Uganda. Methods: A cross-sectional research design employing multi-stage sampling collected data from women aged 15–49 years in Rakai, Uganda, who had been pregnant in the 3 years preceding the survey, conducted between August 10 and December 31, 2013. Additionally, in-depth interviews were conducted. WHO-based disease and management criteria were used to identify MNM. Binary logistic regression was used to predict MNM risk factors. Content analysis was performed for qualitative data. Results: Survey data were collected from 1557 women and 40 in-depth interviews were conducted. The MNM prevalence was 287.7 per 1000 pregnancies; the majority of MNMs resulted from hemorrhage. Unwanted pregnancies, a history of MNM, primipara, pregnancy danger signs, Banyakore ethnicity, and a partner who had completed primary education only were associated with increased odds of MNM (all P  < 0.05). Conclusions: MNM morbidity is a significant burden in Central Uganda. The present study demonstrated higher MNM rates compared with studies employing organ-failure MNM-diagnostic criteria. These findings illustrate the need to look beyond mortality statistics when assessing maternal health outcomes. Concerted efforts to increase supervised deliveries, access to emergency obstetric care, and access to contraceptives are warranted.